2018
DOI: 10.14814/phy2.13921
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements during path integration

Abstract: Self‐motion induces spontaneous eye movements which serve the purpose of stabilizing the visual image on the retina. Previous studies have mainly focused on their reflexive nature and how the perceptual system disentangles visual flow components caused by eye movements and self‐motion. Here, we investigated the role of eye movements in distance reproduction (path integration). We used bimodal (visual‐auditory)‐simulated self‐motion: visual optic flow was paired with an auditory stimulus whose frequency was sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…His eyes focus automatically by means of the lenses accommodating. His retinae turn the incoming imagery into unique patterns of electrical activity, with each glance capturing new imagery to integrate into a seamless pictorial flow ( Churan et al, 2018 ). The optic nerves continuously transfer these signals via his lateral geniculate bodies to his occipital lobes, where analysis of the structure of the scene, in terms of extent, clarity (acuity), brightness, contrast and color takes place within about a tenth of a second ( Lesniak et al, 2017 ), while the adjacent middle temporal lobes capture the flow of movement of the scene ( Zihl and Dutton, 2015 ).…”
Section: The Differences Between Typical Vision and Cortical Or Cerebral Visual Impairmentmentioning
confidence: 99%
“…His eyes focus automatically by means of the lenses accommodating. His retinae turn the incoming imagery into unique patterns of electrical activity, with each glance capturing new imagery to integrate into a seamless pictorial flow ( Churan et al, 2018 ). The optic nerves continuously transfer these signals via his lateral geniculate bodies to his occipital lobes, where analysis of the structure of the scene, in terms of extent, clarity (acuity), brightness, contrast and color takes place within about a tenth of a second ( Lesniak et al, 2017 ), while the adjacent middle temporal lobes capture the flow of movement of the scene ( Zihl and Dutton, 2015 ).…”
Section: The Differences Between Typical Vision and Cortical Or Cerebral Visual Impairmentmentioning
confidence: 99%
“…Our research did not assess the situational constraints of intuitive FOE tracking; for example, task demands might suppress FOE tracking. Churan, von Hopffgarten, and Bremmer (2018) showed that when viewing optic flow stimulus to encode distance traveled, observers showed preferences as to whether they should sample near or farther away from the FOE. Combining an optic flow stimulus with a steering task, Lakshminarasimhan, Avila, Neyhart, DeAngelis, Pitkow, and Angelaki (2020) showed that observers’ eyes tracked an invisible goal for steering rather than the FOE.…”
Section: Discussionmentioning
confidence: 99%
“…For example, task demands might suppress FOE-tracking. Churan, von Hopffgarten, and Bremmer (2018) showed that when viewing optic flow stimulus to encode distance traveled, observers showed preferences in whether they should sample near or further away from the FOE. Combining an optic flow stimulus with a steering task, Lakshminarasimhan, Avila, Neyhart, DeAngelis, Pitkow, and Angelaki (2020) showed that observers' eyes tracked an invisible goal for steering, rather than the FOE.…”
Section: Intuitive Tracking Serves Potential Applicationsmentioning
confidence: 99%